ISLAM LIBERAL DAN KESETARAAN GENDER: REINTERPRETASI PERSPEKTIF AL-QUR'AN DALAM MENJAWAB TANTANGAN KONTEMPORER - Triana, Agis Nita; Qurrotunnisa, Awalia; Najmul Umam, Muhammad Mufti (CV Kalimasada Group, 2024)
The issue of gender equality continues to be an important issue in social and religious discourse, especially in the context of Islamic society. Patriarchal interpretations of religious teachings are often considered to reinforce gender inequality, which leads to discrimination against women in various spheres of life. However, Liberal Islam seeks to overhaul this paradigm through a more inclusive and contextual reinterpretation of Qur'anic verses. This research aims to explore how Liberal Islamic thought provides an alternative in understanding the concept of gender equality in Islam. Using a qualitative method based on text analysis, this research examines the reinterpretation of QS. An-Nisa: 34, which is often considered to support male superiority over women. The results show that reinterpretation based on the values of justice and humanity can correct the gender bias that has dominated the understanding of the text. Liberal Islam proposes a model of equal relations between men and women, both in the domestic and public spheres, while still based on the principles of the Qur'an. This approach is expected to provide solutions to modern social challenges and strengthen the universal values of Islam as rahmatan lil 'alamin